A second-generation anthrax "smoke detector". - Lester, E.D (IEEE Engineering in medicine and biology magazine)
We have demonstrated quantification of aerosolized bacterial spores with a response time of 10 minutes, a sensitivity of 50 spores per liter of air, and a dynamic range of 4 orders of magnitude using a bioaerosol sampler, thermal spore lysis, and a lifetime-gated fluorimeter. This technology is amenable to complete automation and enables long-term, unattended monitoring for airborne bacterial spores. The anthrax spore detector (ASD) technology is envisioned to serve as a front-end monitor that promises tremendous reduction in operating costs for anthrax monitoring at the U.S. Postal Service.